MODEL PEMBELAJARAN CIRC (COOPERATIVE INTEGRATED READING AND COMPOSITION) DALAM MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN TEKS NARASI SISWA KELAS V DI SEKOLAH DASAR - Dhiyaun Nadhira (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
The low reading literacy of Indonesian students, as reflected in the 2022 PISA rankings and the 2020 Minimum Competency Assessment (AKM) results, demands effective learning interventions, particularly in understanding complex narrative texts. This study aims to evaluate the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) learning model in improving fifth-grade elementary school students' narrative reading comprehension skills through the Systematic Literature Review (SLR) method. By analyzing 12 carefully selected articles published between 2020 and 2024, the study's findings consistently demonstrate that the implementation of CIRC contributes significantly to improving students' understanding of narrative elements such as plot, characters, and moral messages. The model's effectiveness is further enhanced when combined with visual media such as picture books and a multimodal approach, and supported by students' reading habits. It is concluded that CIRC is a potential cooperative learning strategy to address literacy deficits by encouraging active interaction and in-depth understanding. Therefore, it is recommended for widespread implementation in the Indonesian language curriculum in elementary schools. ABSTRAK Rendahnya literasi membaca siswa Indonesia, sebagaimana tercermin dalam peringkat PISA 2022 dan hasil Asesmen Kompetensi Minimum (AKM) 2020, menuntut adanya intervensi pembelajaran yang efektif, khususnya dalam memahami teks narasi yang kompleks. Penelitian ini bertujuan untuk mengevaluasi efektivitas model pembelajaran Cooperative Integrated Reading and Composition (CIRC) dalam meningkatkan kemampuan membaca pemahaman teks narasi siswa kelas V sekolah dasar melalui metode Systematic Literature Review (SLR). Dengan menganalisis 12 artikel terbitan 2020–2024 yang telah diseleksi secara ketat, temuan studi ini secara konsisten menunjukkan bahwa penerapan CIRC berkontribusi signifikan terhadap peningkatan pemahaman siswa pada unsur-unsur naratif seperti alur, tokoh, dan pesan moral. Efektivitas model ini semakin optimal ketika dipadukan dengan media visual seperti buku cerita bergambar dan pendekatan multimodal, serta didukung oleh kebiasaan membaca siswa. Disimpulkan bahwa CIRC merupakan strategi pembelajaran kooperatif yang potensial untuk mengatasi defisit literasi dengan mendorong interaksi aktif dan pemahaman mendalam, sehingga direkomendasikan untuk diimplementasikan secara luas dalam kurikulum Bahasa Indonesia di sekolah dasar.